The effect of Medicaid expansion on prescriptions for breast cancer hormonal therapy medications. (17th April 2020) - Maclean, Johanna Catherine; Halpern, Michael T.; Hill, Steven C.; Pesko, Michael F.
Abstract: Objective: To quantify the effects of the Affordable Care Act Medicaid expansion on prescriptions for effective breast cancer hormonal therapies (tamoxifen and aromatase inhibitors) among Medicaid enrollees. Data Source/Study Setting: Medicaid State Drug Utilization Database (SDUD) 2011‐2018, comprising the universe of outpatient prescription medications covered under the Medicaid program. Study Design: Differences‐in‐differences and event‐study linear models compare population rates of tamoxifen and aromatase inhibitor (anastrozole, exemestane, and letrozole) use in expansion and nonexpansion states, controlling for population characteristics, state, and time. Principal Findings: Relative to nonexpansion states, Medicaid‐financed hormonal therapy prescriptions increased by 27.2 per 100 000 nonelderly women in a state. This implies a 28.8 percent increase from the pre‐expansion mean of 94.2 per 100 000 nonelderly women in expansion states. The event‐study model reveals no evidence of differential pretrends in expansion and nonexpansion states and suggests use grew to 40 or more prescriptions per 100 000 nonelderly women 3‐5 years postexpansion. Conclusions: Medicaid expansion may have had a meaningful impact on the ability of lower‐income women to access effective hormonal therapies used to treat breast cancer.